FRI0175 Indirect Treatment Comparisons and Network Meta-Analysis among Biological Agents for Rheumatoid Arthritis: A Systematic Review of Published Literature. (10th June 2014) - Carlos, F.; Aguirre, A.; Naranjo, M.; Gutiérrez, C.; Querol, J.
Abstract : Background: Rheumatoid arthritis (RA) is associated with significant morbidity, functional impairment, loss of quality of life, premature mortality, and substantial economic burden. 1 Biological disease-modifying antirheumatic drugs (bDMARD) are key in the RA treatment pathway. Indirect treatment comparisons (ITC) and network meta-analysis (NMA) allow inferences in the absence of head-to-head comparisons. 2 Objectives: To perform a systematic review of publications of ITC and NMA among bDMARD in RA. Methods: A search in PubMED/Medline and Google Scholar was conducted. Inclusion criteria included full-text access and publication in English or Spanish during a 2009–2013 timeframe. Studies that pooled TNF-α inhibitors and those focused on economic evaluations were excluded. Competing alternatives (either as monotherapy or in combination) were infliximab, etanercept (ETN), adalimumab, certolizumab pegol (CZP), golimumab, abatacept, tocilizumab (TOC), rituximab, and anakinra. Relevant characteristics regarding target population and study design (eg. prior drugs failed and if bDMARD were given as monotherapy or in combination besides its duration) of the selected clinical trials were registered. Trial quality assessment (eg. Jadad scale) and type of statistical approach (frequentist or Bayesian) used when performing ITC or NMA were also recorded. American College of Rheumatology (ACR) 20, 50, and 70 response criteria and withdrawal rates analysed throughout ITC or NMA comprised the outcomes of interest for the present review. Results: Sixty-five references were retrieved, of which 10 achieved inclusion criteria for ITC and NMA. 3–12 The number of clinical trials analyzed in each publication varied from 10 5 to 44. 10 Among the 3 studies that conducted frequentist analyses, 3–5 CZP ranked highest for efficacy in 4 out of 7 efficacy ranking reports, followed by ETN (2) and TOC (1). CZP received the highest efficacy rank in 10 out of 13 ranking reports among the 7 studies with Bayesian approaches, 6–12 while ETN ranked highest in the other 3. ETN was associated with the lowest rates of withdrawal due to adverse events (AEs), 3, 10 whereas CZP showed the lowest rates of withdrawal due to lack of efficacy. 10 Overall, CZP had the lowest rates of all-causes of withdrawal. 10 Conclusions: Current review indicated that published ITC and NMA show that CZP has the highest treatment effect compared to other bDMARD used in RA. In terms of withdrawal rates, ETN had the lowest rates due to AEs, and CZP was associated with the lowest all-cause withdrawal rates. References: Russell A. Pharmacoeconomics 2008;26(10):831-846. Ades et al. Rheumatology (Oxford) 2011;50 Suppl 4:iv5-9. Singh et al. CMAJ 2009;181(11):787-796. Mandema et al. Clin Pharmacol Ther 2011;90(6):828-835. Gallego-Galisteo et al. J Clin Pharm Ther 2012;37(3):301-307. Devine et al. Pharmacotherapy 2011;31(1):39-51. Launois et al. J Rheumatol 2011;38(5):835-845. Turkstra et al. Curr Med Res Opin 2011;27(10):1885-1897. Guyot et al. J Rheumatol 2012;39(6):1198-1206. Desai et al. Ann Pharmacother 2012;46(11):1491-1505. Schmitz et al. BMC Med Res Methodol 2012;12:167. Orme et al. Biologics 2012;6:429-464. Acknowledgements: The authors acknowledge Costello Medical Consulting for editorial assistance which was funded by UCB Pharma. Disclosure of Interest: F. Carlos Consultant for: Roche, MSD, Eli Lilly, UCB Pharma, A. Aguirre Employee of: UCB Pharma, M. Naranjo Employee of: UCB Pharma, C. Gutiérrez Employee of: UCB Pharma, J. Querol Employee of: UCB Pharma DOI: 10.1136/annrheumdis-2014-eular.2512